Identifikasi Mikroplastik Polyethylene (PE) Menggunakan Digesting Wet Peroxide Oxidation (WPO) - Fitriandoni, Adisty; Dewata, Indang (Asian Journal of Science, Technology, Engineering, and Art, 2023)
The extraction method using Wet Peroxide Oxidation (WPO) is a digestion method for separating microplastic particles and other organic/inorganic precipitation, with a liquid oxidation process using peroxide and iron salts as catalysts. Polyethylene (PE) is a type of plastic that pollutes the environment due to its high level of use in the packaging sector. The aim of this research is to determine the optimum conditions for the Wet Peroxide Oxidation (WPO) extraction method and obtain an effective method for identifying microplastics. Variations in oven temperature are 70⁰C, 80⁰C, 90⁰C, 100⁰C, and 110⁰C; variations in Fe(II) concentrsation 0.025 M, 0.05 M, 0.075 M, 0.1 M, and 0.125 M; heating temperature variations 30⁰C, 45⁰C, 60⁰C, 75⁰C, and 90⁰C. The research results showed that the optimum oven conditions occurred at a temperature of 90⁰C producing a microplastic mass of 0.5943 grams, the optimum Fe(II) concentration of 0.1M produced a mass of 1.2966 grams, the optimum heating temperature occurred at 60⁰C producing a mass of 0.7128 grams. For samples, characterization using FTIR showed that no new groups were formed after being treated under optimal conditions. Meanwhile, for XRF, no impurity elements were identified after the sample was treated with optimum conditions.